DETECTION OF FRAUDULENT FINANCIAL STATEMENTS FRAUD HEXAGON S.C.C.O.R.E MODEL APPROACH - Dona Chantia (2021)
This research using quantitative study aimed to analyze effect of Fraud Hexagon S.C.C.O.R.E Model specifically financial stability, external pressure, financial target, capability, collusion, effective monitoring, rationalization, arrogance on fraudulent financial statements. This study uses sample financial sector companies listed Indonesia Stock Exchange 2017 - 2019 with purposive sampling. Acceptable sample size is 89% of population. Hypothesis testing used Logistic Regression Analysis with significant level 0.05. The results that (1) there is significant positive effect of financial stability on fraudulent financial statement meaning more stable company's financial condition, the lower fraudulent financial statements indication, (2) there is significant negative effect of external pressure on fraudulent financial statement meaning more fulfilled company's needs, the lower fraudulent financial statements indication, (3) there is significant negative effect of financial targets on fraudulent financial statement meaning the lower profit, the higher fraudulent financial statements indication, (4) there is no significant effect of capability on fraudulent financial statement, (5) there is no significant effect of collusion on fraudulent financial statement, (6) there is no significant effect of effective monitoring on fraudulent financial statement, (7) there is no significant effect of rationalization on fraudulent financial statement, (8) there is no significant effect of arrogance on fraudulent financial statement. Keywords: fraudulent financial statement; hexagon theory; S.C.C.O.R.E model